Gold investment intention among urban public sector employees in Malaysia - Abdul Wahab, Ahmad Fauzi; Abdul Rahim @ Abdul Wahab, Husniyah; Sabri, Mohamad Fazli; Othman, Mohd Amim; Mohd Rasdi, Roziah (Malaysian Consumer and Family Economics Association, 2016)
Asset accumulation has focused intensely on investment as a tool for elevating income. Gold investment has gained the attention among individuals due to the introduction of new forms of gold investment products. This study applied the Theory of Planned Behaviour to include the construct of gold investment literacy. The potential factors such as attitude, subjective norms, perceived behavioural control and literacy regarding gold investment are determined their significance of influence on gold investment intention. A total of 254 respondents among urban public sector employees in Peninsular Malaysia sampled via a multistage random sampling responded to self-administered questionnaires. Statistical analyses demonstrated moderate levels for gold investment literacy, subjective norms, perceived behavioural control, attitude and investment intention. Multiple regression analysis revealed that gold investment attitude, subjective norms and perceived behavioural control significantly predicted employees’ intention to invest in gold with moderate explained variance (R2 = 0.564) by the predictors. Gold investment literacy however, was not significant in influencing gold investment intention. These findings are useful information that may be incorporated into employees’ development program aimed to improve personal financial behaviour of employees.